2022
DOI: 10.3390/nu14061171
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Diet Induces Depletion of Lactic Acid-Producing Bacteria in Murine Gut

Abstract: Dietary habits are amongst the main factors that influence the gut microbiome. Accumulating evidence points to the impact of a high-salt diet (HSD) on the composition and function of the intestinal microbiota, immune system and disease. In the present study, we thus investigated the effects of different NaCl content in the food (0.03%/sodium deficient, 0.5%/control, 4% and 10% NaCl) on the gut microbiome composition in mice. The bacterial composition was profiled using the 16S ribosomal RNA (rRNA) gene amplico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 66 publications
8
12
1
Order By: Relevance
“…Treatment of Bifico could increase their abundance. From Spearman’s correlation analysis, we found that Actinobacteria phylum and Bifidobacterium genus were positively correlated with propionate, butyrate and valerate, which were consistent with previous report [ 90 ]. Proteobacteria phylum and Muribaculum genus were positively correlated with valerate.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment of Bifico could increase their abundance. From Spearman’s correlation analysis, we found that Actinobacteria phylum and Bifidobacterium genus were positively correlated with propionate, butyrate and valerate, which were consistent with previous report [ 90 ]. Proteobacteria phylum and Muribaculum genus were positively correlated with valerate.…”
Section: Discussionsupporting
confidence: 92%
“…Despite progress in its prevention, its impact continues to be being relevant, and new preventive strategies for IBD are needed ( 30 , 31 ). Several tryptophan metabolites have been identified to protect against inflammation caused by IBDs ( 32 ). IPA is a deamine product of tryptophan that can only be produced by gut bacteria ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study again reveals that a high salt diet led to intestinal aging in mice associated with gut microbiota, further validating the previous relationship that aging and gut microbiota are closely linked. Previous study suggested that HSD disrupts the balance of the intestinal microbiota primarily by depleting lactic acid-producing bacteria in a dose-dependent manner, and that these are important for salt-sensitive inflammatory diseases ( 30 ).…”
Section: Discussionmentioning
confidence: 99%